2014
DOI: 10.1245/s10434-014-3666-x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Learning Curve Associated with Postoperative Morbidity of Laparoscopic Total Gastrectomy for Gastric Carcinoma

Abstract: LTG is a feasible technique with acceptable morbidity and mortality. However, substantial surgical experience is of most importance to reduce postoperative morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 27 publications
3
31
0
3
Order By: Relevance
“…The present study found that postoperative morbidity significantly differed in the elderly, patients with more comorbidities, and those patients who underwent longer operation time. All of these factors had been reported in the previous studies, but the findings were not the same in those studies [27][28][29][30]. This difference may be due to the difference in the definitions of postoperative complications used, the different extents of lymphadenectomy, and the differences in surgeons' experience with the laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The present study found that postoperative morbidity significantly differed in the elderly, patients with more comorbidities, and those patients who underwent longer operation time. All of these factors had been reported in the previous studies, but the findings were not the same in those studies [27][28][29][30]. This difference may be due to the difference in the definitions of postoperative complications used, the different extents of lymphadenectomy, and the differences in surgeons' experience with the laparoscopic surgery.…”
Section: Discussionmentioning
confidence: 81%
“…In 2011, Lee et al [27] first used the Clavien-Dindo system to evaluate the postoperative complications in LDG and open distal gastrectomy. Recently, the incidences of morbidity rates for laparoscopic surgery vary from 11.0 to 25.3 % [27][28][29][30], and the complication rates for LTG are reported to be higher than those for LDG because of technical difficulties. However, in this study, the postoperative morbidity rate in LTG group was 15.1 % and the mortality rate was 0.4 %, which were slightly higher than that in the LDG group, but without statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, our study identified a 30-day mortality rate of 5.2%. While some institutional studies have described zero percent mortality, database and multi-center collaborative studies consistently report significantly higher patient mortality (9, 11, 2228). A recent multi-center study from the US Gastric Cancer Collaborative of 447 sub-total resections for gastric cancer between 2000 and 2012 reported a similar 4.9% mortality rate for all patients (29).…”
Section: Discussionmentioning
confidence: 99%
“…At present, gastric operations are largely resections for cancer or a part of high-volume bariatric subspecialty. Despite this perception, gastrectomy remains an important and morbid general surgery operation (711). A recent NSQIP study evaluating morbidity associated with gastrectomy for gastric cancer identified 5% post-operative mortality after total gastrectomy – higher than current mortality after major hepatectomy or pancreaticoduodenectomy (8, 12, 13).…”
Section: Introductionmentioning
confidence: 99%
“…37 By contrast, Jung et al reported that the first generation of surgeons needed to conduct approximately 100 LTG cases to overcome the learning curve. 38 The first generation of surgeons who performed the technique did not have a standardized procedure or an established training system.…”
Section: Learning Curve Of Ltgmentioning
confidence: 99%